2018
DOI: 10.1111/jdv.14963
|View full text |Cite
|
Sign up to set email alerts
|

Topical propranolol for infantile haemangiomas: a systematic review

Abstract: Infantile haemangiomas are the most common tumour of infancy. Whilst the majority are left untreated to involute spontaneously, residual skin changes commonly occur, particularly in superficial haemangiomas. The current first-line treatment for problematic lesions is oral propranolol; however due to the risk of systemic adverse effects, the use of off-label topical preparations has recently been investigated. Our systematic review was conducted in accordance with PRISMA guidelines. Four databases were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…For further details, see the online supplementary material (see www.karger.com/doi/10.1159/000507808) [11][12][13][14][15][16][17][18][19][20] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further details, see the online supplementary material (see www.karger.com/doi/10.1159/000507808) [11][12][13][14][15][16][17][18][19][20] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery of the effect of propranolol on IHs, oral propranolol is considered the first-line treatment for IHs [7]. In light of the possible adverse effects (AEs) profile of the systemic treatment, topical beta-blockers (bBs), namely propranolol hydrochloride and timolol maleate, are widely used for the treatment of superficial IHs [8][9][10], with an improvement in up to 90% of the cases, minor local AEs, and without any reported systemic AEs [11,12]. The use of lasers, microneedles, as well as radio frequency waves, as topical drug delivery systems can en-DOI: 10.1159/000507808 hance bBs bioavailability, and by that augment the response to the treatment; yet, it might be inapplicable in pediatric population due to their low pain tolerance [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, propranolol was serendipitously discovered to cause regression of proliferating hemangiomas in newborns receiving treatment for other disease [8]. Since then, numerous studies have demonstrated the success of propranolol for shrinking hemangiomas through various forms [9]. Although the specific mechanism has not yet been elucidated, propranolol is more effective than other medical intervention of infantile hemangioma with fewer adverse reactions, and so propranolol gradually replaces those therapies with severe injury and high incidence of complications, and gradually becomes the first-line clinical therapy for infantile hemangioma [10].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment options included in the current treatment strategy of Infantile Hemangioma includes the use of systemic or topical beta-blockers, systemic or intralesional corticosteroids, Interferons, pulsed dye laser therapy, surgical excision etc. The first line agent that is preferred in the treatment of Infantile Hemangioma is propranolol hydrochloride because of its rapid onset of action and good drug tolerability [8]. The orally and intralesionally available therapies are associated with various types of adverse effects, so it is necessary to develop a topical formulation to treat this disease condition.…”
Section: Introductionmentioning
confidence: 99%